Penerapan Model Pembelajaran Aktif dalam Konteks Pendidikan Agama Kristen: Suatu Kajian Terhadap Efektivitasnya dalam Meningkatkan Pemahaman dan Spiritualitas Siswa - Haelitik, Apriana; Dendo, Alviana Maria Tanggu (STAK Reformed Remnant Internasional, 2024)
This research aims to investigate the effectiveness of implementing the active learning model in increasing students' understanding of PAK material and its impact on aspects of students' spirituality. The research method used is qualitative with a library study approach, collecting data from books, journals and the Bible. Implementing an active learning model offers advantages, such as involving students in discussions and physical activities, creating a dynamic learning atmosphere. The focus on active engagement also enhances understanding of theological concepts, creating immersive hands-on experiences. The research results provide insight into the potential of active learning models in the context of PAK, contributing to the development of effective learning strategies. PAK teachers play a crucial role in guiding students not only in academic aspects, but also in character and spiritual development. It is hoped that the findings of this research can become the basis for planning learning that has a positive impact on the development of student character and spirituality in Christian religious educational institutions.